Ameliorate direct power control of standalone wind energy generation system based on permanent magnet synchronous generator by using fuzzy logic control - Lebied, Rima; Lalalou, Rachid; Benalla, Hocine; Nebti, Khalil; Boukhechem, Ismail (Національний технічний університет "Харківський політехнічний інститут", 2020)
Electricity is a basic energy for life and its consumption increased so we need the discovery of new sources of energy such as wind energy .for thisameliorate the quality of generated wind energyby using the intelligent artificial control, this control is made to optimize the performance of three-phase PWM rectifier working.

Електроенергія є основною енергією для життя, і її споживання збільшується, тому нам необхідно відкриття нових джерел енергії, таких як енергія вітру. Для поліпшення якості енергії вітру, що генерується за допомогою управління на основі штучного інтелекту, таке управління призначене для оптимізації продуктивності роботи трифазного ШІМ випрямляча.
Keywords: PWM technique; метод ШІМ